Caracterización de producción y comercialización de leche bovina en Ecuador - Palma Arreaga, Vilma Rocío (2021)
Bovine milk is an essential food in the human diet and its production represents an economic support for families. This product provides nutrients, proteins, vitamins, and minerals useful for the body. The production and marketing are important for the quality of the milk; Therefore, it is necessary to follow a production system that assists livestock production and channels that provide the health of the milk until it reaches the consumer. This document obtained information from books, websites, reports, theses, articles from academic journals, newspaper articles, among others. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose that the reader knows through a summary the characterization of production and commercialization of bovine milk Ecuador. Due to the aforementioned, Raw milk must have the cooling process to be maintained and in the same way go through some tests to determine its quality. it was determined that the production system that is used by the producer dependent on the resources that he has available to him. In addition, it was evidenced that still using the direct channel in rural areas by families, milk is acquired through informal means.